2018
DOI: 10.1111/hel.12516
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Helicobacter pylori infection

Abstract: In this review, we highlight progress in the last year in characterizing known virulence factors like flagella and the Cag type IV secretion system with sophisticated structural and biochemical approaches to yield new insight on the assembly and functions of these critical virulence determinants. Several aspects of Helicobacter pylori physiology were newly explored this year and evaluated for their functions during stomach colonization, including a fascinating role for the essential protease HtrA in allowing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 50 publications
0
61
0
1
Order By: Relevance
“…However, the VapD expression levels detected in all the biopsies were high enough to believe that an important number of vapD-positive H. pylori strains were colonizing both gastric antrum and corpus in all patients. The impact of H. pylori virulence factors on the development of gastroduodenal diseases [3,23,24] is well documented. CagA is an oncoprotein, which is injected into host cells via a pilus structure called type IV secretion system (T4SS) encoded for cag-PAI [3,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the VapD expression levels detected in all the biopsies were high enough to believe that an important number of vapD-positive H. pylori strains were colonizing both gastric antrum and corpus in all patients. The impact of H. pylori virulence factors on the development of gastroduodenal diseases [3,23,24] is well documented. CagA is an oncoprotein, which is injected into host cells via a pilus structure called type IV secretion system (T4SS) encoded for cag-PAI [3,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of H. pylori virulence factors on the development of gastroduodenal diseases [3,23,24] is well documented. CagA is an oncoprotein, which is injected into host cells via a pilus structure called type IV secretion system (T4SS) encoded for cag-PAI [3,23,24]. VacA is a cytotoxin that induces vacuole formation in eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helicobacter pylori (H pylori) infects over half of the world's population and causes a series of gastric diseases including superficial gastritis, chronic atrophic gastritis, and peptic ulcers. 1 Moreover, long-term H pylori infection can lead to gastric malignancies, which have been demonstrated in both human and animal models; thus, H pylori has been recognized as a class I carcinogen by the International Agency for Research on Cancer. 2 Recently, a number of clinical studies have demonstrated that the earlier H pylori eradication therapy is given, especially prior to the development of precancerous lesions, the more effective it will be in reducing the risk of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Two well‐defined clinical entities provide a vivid illustration of disrupted microbiome‐host interactions: Clostridioides difficile‐ associated disease (CDAD) and Helicobacter pylori infection. The former serves as a dramatic reminder of the consequences of iatrogenic disruptions of a microbiome that, when intact, serves to protect us against pathogens (Britton & Young, ; Schäffler & Breitrück, ), and the latter exemplifies how host genome, bacterial properties and the immune response conspire to produce various disease phenotypes (Noto & Peek, ; Thorell, Lehours, & Vale, ; Waskito, Salama, & Yamaoka, ).…”
Section: What Do We Know?mentioning
confidence: 99%